Comparative assessment of management systems in the field of physical education and sports in the brics countries - Dolmatova T.V.; Grebennikov A.I.; Malinin A.V.; Pukhov D.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study to analyze the management system in the field of sports in the BRICS countries. Methods and structure of the study. As part of the scientific work, an institutional approach was used to study the organizational structure of government bodies implementing policies in the field of physical culture and sports in the BRICS countries, using the method of structural analysis, comparative analysis and generalization. Results and conclusions. Using the example of the activities of government authorities in the field of sports, various approaches to organizing a management system in sports are shown in the BRICS countries, where some countries implement the classical approach to management headed by the relevant government body in the field of physical culture and sports (Russian Federation, South Africa), and others, in addition, have specialized second-level departments that perform the role of specialized government agencies (Brazil, India, China). At the same time, within each of the identified models there are specific features of the organization of the management system in sports, which is due to the specifics of the regulatory system, socio-economic development and national culture of each country.